Treatment of CMV infection after allogeneic hematopoietic stem cell transplantation. Issue 6 (2nd June 2016) - Maffini, Enrico; Giaccone, Luisa; Festuccia, Moreno; Brunello, Lucia; Busca, Alessandro; Bruno, Benedetto
ABSTRACT: Despite a remarkable reduction in the past decades, cytomegalovirus (CMV) disease in allogeneic hematopoietic stem cell transplant (HSCT) recipients remains a feared complication, still associated with significant morbidity and mortality. Today, first line treatment of CMV infection/reactivation is still based on dated antiviral compounds Ganciclovir (GCV), Foscarnet (FOS) and Cidofovir (CDF) with their burdensome weight of side effects. Maribavir (MBV), Letermovir (LMV) and Brincidofovir (BDF) are three new promising anti-CMV drugs without myelosuppressive properties or renal toxic effects that are under investigation in randomized phase II and III trials. Adoptive T-cell therapy (ATCT) in CMV infection possesses a strong rationale, demonstrated by several proof of concept studies; its feasibility is currently under investigation by clinical trials. ATCT from third-party and naïve donors could meet the needs of HSCT recipients of seronegative donors and cord blood grafts. In selected patients such as recipients of T-cell depleted grafts, ATCT, based on CMV-specific host T-cells reconstitution kinetics, would be of value in the prophylactic and/or preemptive CMV treatment. Vaccine-immunotherapy has the difficult task to reduce the incidence of CMV reactivation/infection in highly immunocompromised HSCT patients. Newer notions on CMV biology may represent the base to flush out the Troll of transplantation.